Beyond Co-Expression: Unraveling the Complex Relationship Between PD-L1 and Tumor-Infiltrating Lymphocytes in Basal Cell Carcinoma Subtypes - Fitria Mayasari; Kenty Wantri Anita; Diah Prabawati Retnani; Rachmad Sarwo Bekti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Basal cell carcinoma (BCC) is the most prevalent non-melanoma skin cancer, characterized by high recurrence rates. Immunotherapy, particularly targeting the Programmed Death-1 (PD-1)/Programmed Death-Ligand 1 (PD-L1) axis, offers a promising therapeutic avenue. The interplay between PD-L1 expression on tumor and immune cells and the nature of Tumor-Infiltrating Lymphocytes (TILs) is crucial for immune response, yet their relationship in BCC, especially across diverse histological subtypes, remains incompletely understood. This study aimed to investigate the correlation between PD-L1 expression and TILs density in various BCC subtypes, seeking to elucidate the complexities of their interaction within the tumor microenvironment. Methods: This analytical observational study utilized a cross-sectional design, analyzing 20 archived paraffin-embedded BCC tissue samples from Dr. Saiful Anwar Regional General Hospital Malang. PD-L1 expression was assessed by immunohistochemistry using the 22c3 clone and evaluated via the Combined Positive Score (CPS). TILs were semi-quantitatively assessed as percentage infiltration and categorized into low, moderate, and high grades. Histological subtypes of BCC were documented. Spearman correlation was used to analyze the relationship between PD-L1 expression and TILs. Results: Of the 20 BCC cases, 55% exhibited PD-L1 positivity (CPS ≥ 1). TILs infiltration was predominantly moderate (70%), with 25% high and 5% low. The cohort included nodular (40%), infiltrating (35%), and basosquamous (25%) as the main subtypes, with specific variants also analyzed. Basosquamous BCC consistently showed positive PD-L1 expression (100% of its cases positive), while nodular and infiltrating subtypes displayed varied PD-L1 expression. TILs distribution also varied across subtypes, with nodular BCC exhibiting the full range from low to high TILs. Overall, no significant correlation was observed between PD-L1 expression and TILs density (Spearman's r = -0.077, p = 0.747). Conclusion: This study confirms PD-L1 expression and TILs presence in BCC but reveals no direct linear correlation between them across the cohort, even when considering broad subtypes. Basosquamous BCC consistently expressed PD-L1. The lack of overall correlation suggests a complex, potentially subtype-specific interplay within the BCC tumor microenvironment, warranting further investigation into functional TILs subsets and other immune modulators.